Implementing of Educational Institution Management - Elihami Elihami; Syawal Syawal (Universitas Muhammadiyah Enrekang, 2022)
The leadership and managerial ability of the leadership of the management of the As'adiyah Sengkang educational institution which is one of the determining factors for the development of the educational institution. This study aims to describe the portrait of As'adiyah Sengkang's educational management in developing educational institutions. This study uses a qualitative approach. Data collection methods are observation, in-depth interviews and documentation. Data were analyzed by data reduction, presentation, and verification. The results showed that the decision system of the leadership of the As'adiyah Sengkang educational institution did not adhere to an openness system that tended to be closed and the pattern of appointing management staff was still in the process of developing professionalism and the management pattern in policy decisions was centered on the highest leadership. This shows that the As'adiyah Sengkang educational institution is to carry out managerial functions of educational management in planning, organizing, implementing and evaluating as well as monitoring in a more professional development process. The educational process that occurs is adaptive in accordance with future educational conditions and challenges. So it can be concluded that the As'adiyah Sengkang educational institution is in a good category in the managerial process but still needs a more comprehensive and adaptive improvement by following the development of the 4.0 education era without reducing local wisdom which is a special advantage towards society 5.0.